Water waves and ship hydrodynamics an introduction - Hermans, A. J. (Springer, 2011)
In this book an introduction is given to aspects of water waves that play a role in ship hydrodynamics and offshore engineering. Finally an introduction to the theory of shallow water non-linear dispersive waves is presented, and shallow water ship hydrodynamics, that plays a role in coastal areas and channels is treated.